Acidic deposition - "Harter, P" (IEA Coal Research,London, UK, 1989)
The acidification of soft water aquatic ecosystems, with consequent damage to the flora and fauna, is considered in this report. The evidence that environmental effects are occurring is examined to see if a trend of increasing acidification can be related to changes in atmospheric deposition of sulphates and nitrates. Possible causes of change are considered, to clarify the contributions of variations in human activities and natural factors. It is concluded that acidic deposition, originating partly from emissions of sulphur and nitrogen compounds arising from man-made sources including combustion of fossil fuels, is causing acidification of surface waters in some areas of Europe and North America. There is proof that acidification of surface waters (to less than pH 6) is deleterious to many of the organisms whose habitat it forms. Acidified surface waters in some of the impacted areas are showing signs of recovery, where emissions of sulphur and nitrogen compounds from human activities are decreasing. There is some evidence that reversibility of acidification has started to occur, in some instances, about a decade after emissions were reduced. The scope of the report is confined to the scientific evidence of ecological effects and thus excludes policy considerations and details of control strategies. 220 refs., 13 figs., 9 tabs.
Keywords: "54 ENVIRONMENTAL SCIENCES"; "01 COAL, LIGNITE, AND PEAT"; "ACID RAIN"; "ENVIRONMENTAL EFFECTS"; "AQUATIC ECOSYSTEMS"; "ACIDIFICATION"; "SURFACE WATERS"; "AIR POLLUTION"; "AQUATIC ORGANISMS"; "EUROPE"; "FOSSIL FUELS"; "NITRATES"; "NORTH AMERICA"; "REVIEWS"; "SULFATES"; "WATER CHEMISTRY"; "ATMOSPHERIC PRECIPITATIONS"; "CHEMISTRY"; "DOCUMENT TYPES"; "ECOSYSTEMS"; "ENERGY SOURCES"; "FUELS"; "NITROGEN COMPOUNDS"; "OXYGEN COMPOUNDS"; "POLLUTION"; "RAIN"; "SULFUR COMPOUNDS"; "500200* - Environment, Atmospheric- Chemicals Monitoring & Transport- (-1989)"; "010900 - Coal, Lignite, & Peat- Environmental Aspects"